EXAMINING THE FORMATION OF ATTITUDINAL, CONATIVE, AND BEHAVIOURAL LOYALTY: AN EMPIRICAL ANALYSIS IN THE HOTEL INDUSTRY - SUHARTANTO, DWI (ITB Journal Publisher, LPPM ITB, 2013)
This study examines the dimensional structure of the brand loyalty construct in the hotel industry context. Following recent developments in loyalty studies, brand loyalty is proposed as a three-dimensional construct consisting of attitudinal loyalty, conative loyalty, and behavioural loyalty. In addition to directly affecting behavioural loyalty, attitudinal loyalty influences behavioural loyalty indirectly through conative loyalty. This conceptualisation is supported by the statistical analysis and provides an improved of the brand loyalty construct compared to the existing conceptualisations, such as fourstage, three-stage, and two-stage brand loyalty models. This study provides an important contribution in extending an understanding of the complex structure of brand loyalty, especially in a hotel industry context.